2019
DOI: 10.24996/ijs.2019.60.11.18
|View full text |Cite
|
Sign up to set email alerts
|

On Rickart Modules

Abstract: Gangyong Lee, S.Tariq Rizvi, and Cosmin S.Roman studied Rickart modules. The main purpose of this paper is to develop the properties of Rickart modules . We prove that each injective and prime module is a Rickart module. And we give characterizations of some kind of rings in term of Rickart modules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…It has been reported that greywater is a good environment for the growth of six different species of bacteria [9]. The problem is that the design of the air conditioner unit does not include recycling this water, exposing it to contamination from the air.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been reported that greywater is a good environment for the growth of six different species of bacteria [9]. The problem is that the design of the air conditioner unit does not include recycling this water, exposing it to contamination from the air.…”
Section: Literature Reviewmentioning
confidence: 99%